Management of Polaron Dynamics: A Key Factor for the Long Operational Stability of Exciplex‐Forming Cohost‐Based Organic Light‐Emitting Diodes. Issue 1 (1st November 2022) - Lee, Kyung Hyung; Jeon, Soon Ok; Chung, Yeon Sook; Kim, Jae‐Min; Lee, Jun Yeob
Abstract: The device performance of phosphorescent organic light‐emitting diodes (PHOLEDs) is improved by using the exciplex‐forming cohost with the thermally activated delayed fluorescence (TADF) property. This work comprehensively investigates the excitons and polarons management of exciplex host and dopant to understand the device degradation of PHOLEDs with various host materials. The recombination and accumulation of polarons is newly integrated in the numerical model for understanding transient electroluminescence in order to theoretically characterize a diversity of the polaron dynamics. Based on the unique excitons kinetics, polarons kinetics, and recombination coefficients coming from the exciplex host materials, the device degradation is examined. As a result, it is revealed that the longer device lifetime is attributed to the suppression of the exciton–polaron interaction by minimizing the steady‐state polarons via fast polaron recombination. The combination of the exciton–polaron coupled kinetics model and the device degradation model show that the recombination coefficient should be considered a key parameter of the host materials to design long‐lived PHOLEDs. Abstract : The recombination and accumulation of polarons are investigated by the numerical model for transient electroluminescence. These are induced by the different recombination coefficients and degradation mechanisms. As a result, it is demonstrated that the longer device lifetime is attributed to the suppression of the exciton–polaron interaction via fast polaron recombination.